2011
DOI: 10.26719/2011.17.11.825
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the health-related quality of life of Emirati people with diabetes: integration of sociodemographic and disease-related variables

Abstract: This study aimed to evaluate the health-related quality of life (HRQOL) of Emirati people with diabetes and to explore the sociodemographic and disease-related variables affecting it. The Arabic version of the World Health Organization quality of life questionnaire, short version (WHOQOL-BREF) was administered to 200 people with diabetes. The overall mean score was 63.1 (SD 15.0), ranging from 61.5 to 65.5 on subscales. Three factors significantly influenced the total HRQOL: presence of diabetes complications,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
44
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 17 publications
14
44
3
Order By: Relevance
“…Results of the univariate analysis revealed that, in line with earlier research findings, patients who have multiple chronic conditions and those with diabetes complications manifested as ASCVD were found to have lower HRQoL. However, both variables were not significantly associated with HRQoL scores in the multiple regression analysis in the current study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Results of the univariate analysis revealed that, in line with earlier research findings, patients who have multiple chronic conditions and those with diabetes complications manifested as ASCVD were found to have lower HRQoL. However, both variables were not significantly associated with HRQoL scores in the multiple regression analysis in the current study.…”
Section: Discussionsupporting
confidence: 86%
“…Similar to the current study findings, an earlier cross‐sectional study conducted in East China reported a moderate HRQoL for patients with type 2 diabetes with a mean EQ‐5D index of 0.736 (SD 0.12) . Another study, which used the short version of the WHO (WHOQOL‐BREF) questionnaire, reported a total mean score of 0.631 (SD 0.15) for the overall HRQoL in Emirati people with diabetes . However, a much lower EQ‐5D index was reported by Iqbal et al .…”
Section: Discussionsupporting
confidence: 86%
“…The social domain was found to be significant in the present study group with a mean score of 12.13 (SD± 2.5). In our study for, WHOQOL-BREF, social domain scored lowest which is consistent with the study done in Belapatel, et al 9 whereas these results are in contrast toBani-Issa W. et.al 19 .Where social and environmental scored highest. These differences depict socio-cultural differences between two countries.…”
Section: Assessment Of Qol In Study Participantssupporting
confidence: 91%
“…The physical domain in this study population is found to be insignificant as obtained p-value is >0.05. This result is in contrast when compared to another study fromBelapatel, et al 9 Whereas this result is consistent with the study done byBani-Issa W. et.al 19 The above differences in the mean score of health related QoL and its domains in the diabetic subjects arestrong proof that the healthrelatedQoL is a subjective concept and is perceived differently by each individual in a different culture. Good awareness of diabetes, diet adherence, and less co-morbid conditions contributed patients to score 'good' in the physical domain, whereas these aspects lack in patients who scored 'average' in this domain in the uncontrolled diabetic group.…”
Section: Assessment Of Qol In Study Participantssupporting
confidence: 87%
“…In patients with diabetes mellitus, in our study, mean score for the psychological domain of quality of life was lower (mean score 56.28 ± 14.88) than in patients with diabetes mellitus in studies in Denmark (mean score 71.2) [21] and Emirates (mean score 61.5 ± 13.7) [22], and higher than in studies in Serbia (mean score 55.26 ± 19.2) [23], Iran (55.67 ± 11.96) [24], as well in African-Americans in Maryland, followed by the SF -36 (mean score 69 ± 21) [25]. In our study, mean score of psychological domain of quality of life were higher in male compared to female respondents, but without statistically significant difference.…”
Section: Discussioncontrasting
confidence: 62%